The use of tense and aspect in isiZulu and English by isiZulu L1/English L2 speakers: An empirical investigation. Issue 3 (1st October 2020) - Sibisi, Muhle; Tappe, Heike
ABSTRACT: Past research indicates that the acquisition and subsequent usage of tense/aspect markings by second language (L2) speakers pose particular challenges. Such challenges may emanate, inter alia, from differences in the tense/aspect systems of a L2 speaker's two languages. This article compares and contrasts the use of tense and aspect in isiZulu and English by isiZulu L1/ English L2 speakers. We conducted an empirical intra-individual study among first-year mechanical engineering students enrolled for a communication skills module at a university of technology. The participants produced two written reports on a hypothetical series of events which culminated in an imaginary laboratory accident. We investigate how similarities and differences between English and isiZulu manifest in the written reports of each student. The qualitative, intra-individual data analysis indicates that our participants carefully position the events on a linear timeline and that they encode the chronological succession of these events in detail in their L1. In contrast, these abilities are less apparent in the L2. Here, the chronological order of events is less clear because the students tend to 'simplify' the available L2 tense/aspect system; in particular, they seem to avoid the English inflectional morphology '-en' (aux+ -en). Thus, English L2 students may be supported by (1) allowing space for the L1 to impact on the learning of the L2, and by (2) engaging students through custom-made, contextualised simulation activities that reinforce the use of English tense and aspect. Furthermore, our research supports transformative language policies and a promotion of African languages inside and outside academia.